Multithreading Prioritization Concurrently by using an Effective Dynamic Slicing Algorithm - Maysoon, A. Mohammed; Mazlina, Abdul Majid; Mohammed Adam, Ibrahim Fakharaldien; Balsam, A. Mustafa (2014)
Lately, multithreading evolved into a standard way to enhance the processor usage and program efficiency. The dynamic program slice can be that component of an application that affects the working out of an adjustable regarding interest throughout program performance over a certain system input. Dynamic program slicing describes an amount of program slicing techniques that depend on program execution and may even significantly decrease the size of an application slice simply because run-time data, accumulated during program execution, is used in order to figure out system slices. Three related methods to multithreading prioritization are introduced in this paper.